2009
DOI: 10.1139/w09-036
|View full text |Cite
|
Sign up to set email alerts
|

Amplified ribosomal DNA restriction analysis of free-living bacteria present in the headbox of a Canadian paper machine

Abstract: The headbox water is the main source of bacterial contamination of paper machines. Identification of these bacterial contaminants could be an asset in developing specific control methods. An amplified ribosomal DNA restriction analysis (ARDRA) was carried out to characterize the bacterial communities associated with the headbox water of a paper machine in a Canadian mill in February and July 2006. Eight bacterial genera were identified as the main colonizers present in the headbox water. The genus Meiothermus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…In vivo, proteins of desiccation-resistant bacteria were protected from oxidative modifications that introduce carbonyl groups in sensitive bacteria during drying. Members of Chelatococcus have also been identified among other genera present in the headbox water of a paper machine in Canada (Prince et al 2009), using an amplified ribosomal DNA restriction analysis.…”
Section: Ecologymentioning
confidence: 99%
“…In vivo, proteins of desiccation-resistant bacteria were protected from oxidative modifications that introduce carbonyl groups in sensitive bacteria during drying. Members of Chelatococcus have also been identified among other genera present in the headbox water of a paper machine in Canada (Prince et al 2009), using an amplified ribosomal DNA restriction analysis.…”
Section: Ecologymentioning
confidence: 99%
“…This bacterium has been shown prevalent in the water circuits of many pulp and paper mills [9,22,25,26]. We showed that the white water bacteria Psx.…”
Section: Introductionmentioning
confidence: 83%
“…Pseudoxanthomonas taiwanensis is a frequent and abundant contaminant of paper machines [9,22,31]. Abietic acid was used as the model resin acid because it is a major component in spruce wood pitch [15,32].…”
Section: Discussionmentioning
confidence: 99%